2022
DOI: 10.3390/machines10070545
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Parametric Adaptive Hybrid Active–Passive Training Control Method for Rehabilitation Robot

Abstract: Rehabilitation robots facilitate patients to take part in physical and occupational training. Most of the rehabilitation robots used in clinical practice adopt pure passive training or active training, which cannot sense the active participation of patients during passive training and lack adaptive dynamic adjustment of training parameters for patients. In this paper, an intelligent hybrid active–passive training control method is proposed to enhance the active participation of patients in passive training mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The robot can be adjusted to different sizes and support positions according to individual patient differences. During use, the patient is placed in a sitting or lying position with both feet on the pedals of the mechanical leg, the centers of the joints of the lower limbs are aligned with the centers of rotation of the robot joints, and the body is fixed to the robot through safety straps and aids to prevent secondary injuries caused by overturning during the training process [16]. In this study, tension pressure sensors were used to identify HMI forces [17], as shown in Figure 2, with pressure sensors on the thigh, shank, and plantar.…”
Section: Mechanical Design and Sensor Systems For Of Lebotmentioning
confidence: 99%
“…The robot can be adjusted to different sizes and support positions according to individual patient differences. During use, the patient is placed in a sitting or lying position with both feet on the pedals of the mechanical leg, the centers of the joints of the lower limbs are aligned with the centers of rotation of the robot joints, and the body is fixed to the robot through safety straps and aids to prevent secondary injuries caused by overturning during the training process [16]. In this study, tension pressure sensors were used to identify HMI forces [17], as shown in Figure 2, with pressure sensors on the thigh, shank, and plantar.…”
Section: Mechanical Design and Sensor Systems For Of Lebotmentioning
confidence: 99%
“…Examples include standing lower limb rehabilitation robots Lokomat [4], ReWalk [5], and Ailegs [6], as well as sitting lower limb rehabilitation robots Motion Maker [7,8], LR2 [9], and LRR-Ro [10]. These rehabilitation robots can provide passive training, active training, and auxiliary training [11]. The sitting and lying lower limb rehabilitation robot can reduce the unnecessary weight load on the body and improve the comfort of the person, as well as facilitate exercise and increase the range of motion of the lower limb joints.…”
Section: Introductionmentioning
confidence: 99%